The effect of physical education teacher competencies on enhancing middle school students learning motivation - Sadi , Sadi Mohammed (sports creativity, 2025)
This study aims at achieving a primary step to find out and spot some teaching competencies of PE teachers( physical education teacher) and its effects on students' learning motivation, Consequently, the importance of this study contributes theoretically and practically in enhancing and improving students' learning motivation. For this reason, we adopted a descriptive approach, Our sample is composed of 200 students from middle school who were chosen randomly of both genders,Our research tools were about a questionnaire that measures students' learning motivation and an observation of physical education teacher performance, The study indicates that: - Physical Education teacher' Classroom management competencies affects middle school students' learning motivation. - Physical Education teacher' s assessment competencies affects middle school students' learning motivation